Experimental Study of Static and Fatigue Behavior of CFRP-Balsa Sandwiches under Three-point Flexural Loading - Zaharia, Sebastian Marian; Morariu, Cristin Olimpiu; Nedelcu, Anisor; Pop, Mihai Alin (BioResources, 2017)
Balsa wood is a natural cellular material with an excellent resistance-toweight ratio that is ideal for manufacturing the core of sandwich structures. In this study, sandwich specimens with a carbon-fiberreinforced polymer (CFRP) skin and a balsa wood core were tested with static and dynamic loading. Three-point flexural tests in static regime determined the mechanical characteristics of the CFRP-balsa specimens that were needed for subsequent fatigue strength tests. Also, experimental research was performed on the Charpy impact response of the CFRP-balsa sandwich specimens. This study implemented an accelerated fatigue testing method to identify and predict the mean fatigue life of the CFRP-balsa sandwich specimens subjected to cyclic fatigue via three-point flexural tests. Using the accelerated fatigue and the three-point flexural testing methodology on the CFRP-balsa sandwich specimens, the testing period was reduced by 11.9 times, and thus the material costs necessary for the tests were also reduced. Also, the breaking surfaces were analysed to reveal the failure modes of CFRP-balsa specimens subjected to static and fatigue tests at threepoint flexural and at impact tests.
Keywords: Balsawood; CFRP; Sandwich structure; Three-pointflexural test; Mean fatigue life; Accelerated fatigue test